Glicerol na dieta de tilápias do Nilo (Oreochromis niloticus) - Neu, Dacley Hertes (2011)
The higher cost of production at a fish culture is related to nutrition of animals that pass of 50%, so, two experiments were conducted based on digestibility and inclusion of glycerol for the Nile tilapia (Oreochromis niloticus). The purpose of this study was to evaluate digestibility of three sources of glycerol, crude vegetable oil (GBV), semi-purified mixture glycerol (GSM) and semi-purified plant glycerol (GSV) (experiment 1) and then determine to what level of inclusion that food can be held in diets for tilapia and whether it causes changes in blood chemistry characteristics and centesimal composition of animals (experiment 2). In experiment 1, we used 40 fish with mean weight of 343,12 ± 77,71 g distributed in four tanks with 180 liters conical bottom, in a randomized Latin square design. Four experimental diets were prepared, one reference and three tests, composed with the inclusion of 20% of the test food and 80% of the reference diet. Chromic oxideIII was used as inert indicator (0,1% of diet). We obtained the digestible energy of crude glycerol vegetable oil (GBV), semi-purified mixture glycerol (GSM) and semi-purified plant glycerol (GSV) of 3058,55; 2610,55; 1754,70 kcal.kg-1, respectively. For experiment 2, we used the glycerol that contained higher amount of digestible energy (GBV) and it was made five diets containing increasing levels of glycerol (0,0; 2,5; 5,0; 7,5 and 10%) for 79 days and provided to 300 juveniles of Nile tilapia with mean weight of 29,15 ± 8,40 g and 11,55 ± 0,87 cm in length. After this period has evaluated the performance of animals by final weight (FW), length (FL), survival (S), weight gain (WG), feed conversion (FC), specific growth rate (SGR) factor condition (FC), hepatosomatic index (IHS) and visceral fat (VF). For the evaluation of blood biochemical parameters were evaluated protein (PROT), triglycerides (TRIG), cholesterol (COLE), HDL lipoprotein, glucose (GLUC) and VLDL and LDL lipoproteins. To determine the chemical composition were evaluated moisture, lipids, protein and ash. There was no statistical difference between the different treatments on the growth performance of animals. For the biochemical parameters of HDL lipoprotein was only statistically significant difference (P<0.05), being higher in the groups fed with 0,0 and 7,5%, did not differ from animals that were fed 5,0 and 10,0%. For the centesimal composition of tilapia juvenile differences were observed in the amount lipids (P<0.05), which had the highest values in fish fed with 5,0% glycerol. Can be included 10% of the foodl that does not occur any damage to animal health.